Seasonal pattern in food gathering of the weaver ant Oecophylla longinoda (Hymenoptera: Formicidae) in mango orchards in Benin - Vayssières, Jean-François; Ouagoussounon, I.; Adandonon, A.; Sinzogan, A.A.C.; Korie, S.; Todjihounde, R.; Alassane, S.; Wargui, R.B.; Anato, F.M.; Goergen, Georg E. (Informa UK Limited, 2015)
Prey capture and food scavenging activities of Oecophylla longinoda were monitored through regular weekly samplings during two consecutive years (2009–2010) in a large mango orchard of the Borgou Department of Benin, West Africa, a main mango production area located in the Sudan agro-ecological zone. In both years, interspecific competition with other ants occurred mainly during the dry season (January to March) resulting in increased captures of Formicinae, Myrmicinae and Ponerinae. More prey was caught during the rainy season (end April to end October) than during the rest of the year, with Diptera and Coleoptera prey peaking in May and June, respectively, along with the mango season. As insect prey quickly decreased during November to December weaver ants increasingly collected seeds and plant debris. A total of 241 species of insects were captured including 61 species (25.3%) associated with mango and a few with cashew, among which 48 mango pest species (78.7% of species associated with mango tree). Only five species (2.1%) of beneficial insects were captured. It is concluded that the presence of O. longinoda colonies is beneficial to perennial tree cropping systems such as mango and cashew.